2015
DOI: 10.1016/j.psychres.2014.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Living with tics: Reduced impairment and improved quality of life for youth with chronic tic disorders

Abstract: Pharmacological and behavioral interventions have focused on reducing tic severity to alleviate tic-related impairment for youth with chronic tic disorders (CTDs), with no existing intervention focused on the adverse psychosocial consequences of tics. This study examined the preliminary efficacy of a modularized cognitive behavioral intervention ("Living with Tics", LWT) in reducing tic-related impairment and improving quality of life relative to a waitlist control of equal duration. Twenty-four youth (ages 7–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 61 publications
3
52
1
2
Order By: Relevance
“…Of note, the findings of clinical studies published in the last few years suggested the potential efficacy of broader interventions focused on the adverse psychosocial consequences of tics (36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the findings of clinical studies published in the last few years suggested the potential efficacy of broader interventions focused on the adverse psychosocial consequences of tics (36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a need for more comprehensive interventions to reduce the distress, impairment and associated problems experienced by youth with TD (e.g., social problems, social deficits, peer victimization, self-concept) that may be contributing to the development of anxiety and/or depressive symptoms. Although recognized as important in practice parameter guidelines (Murphy et al, 2013), there have been only two studies that have sought to address these co-occurring concerns (McGuire et al, 2015a; Storch et al, 2012b). Beyond interventions to address these problems, future longitudinal data are needed to conclusively assesses the relative impact of tics, anxiety and depressive symptoms on SI in youth in order to fully elucidate the level of risk posed by these emotional symptoms, as well as evaluate the impact of evidence-based interventions on tic severity and emotional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tic reduction may not be the only path to positive global outcome. Intervention targeting tic-related psychosocial problems has shown initial promise in improving quality of life and psychosocial functioning in youth with tics (McGuire et al, 2015). Reducing tics may not have the desired effect of reducing impairment in school, and this intervention does not give recommendations regarding communications with schools.…”
Section: Utilitymentioning
confidence: 99%